School Rules Discipline: A Narrative Study on Elementary School Students in Martapura City - Mubarok Mubarok; Bagus Aulia Iskandar; Zulparis Zulparis; Novi Nurdian (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
This study aims to describe how elementary school children exercise discipline in holding temporary desires and himmah in realizing desires. In describing it, researchers use the basic theory of Good (1959) and supporting theories from Hartati (2010) and Haidar (2013) which define discipline as self-control in an effort to resist momentary desires and the use of desires and abilities. Researchers use a qualitative approach with narrative design. Participants were taken from grade 5 elementary school students with the condition that they met the predetermined participant criteria. In taking data, researchers use interview techniques with reference to interview guidelines that have been made.The results showed that: (1) Elementary school age children are still at a concrete operational stage which leads to a rudimentary state of thought and emotional stability. Children are only able to think logically about abstract objects around them. External influences are very easy to enter the mind and change its movements. The usual influences received by elementary-age children such as skipping school, smoking, and the habit of staying up late. (2) Desire and ability are two things that are interrelated and influence. Desire is related to the goals to be achieved when the child grows up. While ability is related to the facilities available. A child's goals are influenced by two things: personal experience and external encouragement. Meanwhile, ability is influenced by school policies that encourage school literacy.